BMJ Impact Analytics - Neilson, Simon (Septentrio Conference Series, 2023)
Research that improves patients' lives matters deeply to the funders, institutions and researchers who dedicate their resources to medical and health research. As part of our vision for a healthier world, BMJ engaged with the medical and health research community about the evidence that demonstrates genuine real-world impact and how it can be discovered. In the course of this research, many research managers in health and medicine shared the related challenges that they face with information overload, time, and data quality. It became apparent that AI and Machine Learning can help with finding and tracking vital evidence of real-world impact and also answering questions about research performance and strategies. BMJ began collaborating with Overton to create a prototype that was tested extensively with funders, institutions and researchers.